Highly-sensitive Label-free Differential Pulse Voltammetric Immunosensor for Diagnosis of Infectious Diseases Based on Electrospun Copper Doped ZnO Nanofiber Biosensing Platform. (2017) - Paul, K. Brince; Kumar, Sanni; Tripaty, Suryasnata; Singh, Vikrant; Vanjari, Siva Rama Krishna; Singh, Shiv Govind
Abstract: Rapid detection of infectious diseases has generated significant interest in recent years. The time consuming and costly conventional diagnostics methods substantiate the need to develop a cost-effective rapid infectious disease detection platform to address the persistently threatening health issues in developing countries. The recent advancements in nanotechnology and biosensing have manifested the potential to deliver an effective point-of-care diagnostics platform. In this work, the synthesis and fabrication of an ultrasensitive Copper doped Zinc oxide nanofiber based biosensing platform is reported. Copper doped Zinc oxide nanofibers are synthesized by simple electrospinning technique with fiber diameter of 100-200 nm. The structural and morphological characteristics of the nanofibres are studied using X-ray diffraction and field emission scanning electron microscopy. The label free detection of HRP2 protein with the Copper doped Zinc Oxide nanofiber has been investigated by Differential pulse voltammetric technique. Mercaptopropionic acid treatment of Copper doped Zinc oxide nanofiber generates carboxylic acid groups, which facilitate the covalent conjugation of Anti-HRP2. To the best of our knowledge, the fabricated immunosensor displays better sensitivity than the best malaria sensor reported in the literature based on different nanomaterials and different detection mechanism. The proposed platform exhibits very low limit of detection of 10 attogram per ml for the targeted HRP2 protein in a wide detection test range (ag/ml -μg/ml). The novel biosensor platform demonstrates good stability and selectivity which can be implemented for point-of-care diagnosis of biomarkers related to other infectious diseases.